The Course of Physical Capacity in Wheelchair Users During Training for the HandbikeBattle and at 1-Yr Follow-up. (4th September 2021) - Kouwijzer, Ingrid; Valent, Linda J.M.; Post, Marcel W.M.; Wilders, Lise M.; Grootoonk, Anneke; van der Woude, Lucas H.V.; de Groot, Sonja
Abstract : Supplemental digital content is available in the text. Abstract : Objective: The aims of this study were (1) to compare physical capacity at 1-yr follow-up with physical capacity before and after the training period for the HandbikeBattle event and (2) to identify determinants of the course of physical capacity during follow-up. Design: This was a prospective observational study. Former rehabilitation patients ( N = 33) with health conditions such as spinal cord injury or amputation were included. A handcycling/arm crank graded exercise test was performed before (January, T1) and after the training period (June, T2) and at 1-yr follow-up (June, T4). Outcomes were peak power output (W) and peak oxygen uptake (L/min). Determinants were sex (male/female); age (years); classification; physical capacity, musculoskeletal pain, exercise stage of change, and exercise self-efficacy at T1; and HandbikeBattle participation at T4. Results: Multilevel regression analyses showed that peak power output and peak oxygen uptake increased during the training period and did not significantly change during follow-up (T1: 112 ± 37 W, 1.70 ± 0.48 L/min; T2: 130 ± 40 W, 2.07 ± 0.59 L/min; T4: 126 ± 42 W, 2.00 ± 0.57 L/min). Participants who competed again in the HandbikeBattle showed slight improvement in physical capacity during follow-up, whereas participants who did not compete again showed a decrease. Conclusion: Physical capacity showed an increase during the training period and remained stable after 1-yr follow-up. Being (repeatedly) committed to a challenge might facilitate long-term exercise maintenance.